EDGE DETECTION THROUGH FUZZY INFERENCE SYSTEM (International Journal of Engineering and Computer Science, 2013)
this paper fuzzy inference system (FIS) used to detect edges. FIS is very simple and efficient method; identify the edge without determining a threshold value. This paper is concerned with the change of fuzzy logic rules recognized method which will be capable to detect the edges of image. FIS gives single output value corresponding to multiple input values and identifying the pixel, it is an edge pixel. Fuzzy inference system in MATLAB environment has been developed which gives the output result of the input values used as membership functions